Analysis Financial Optimization Strategies for the Success of Polbeng Business Expo Chapter II - Taherah, Putri; Astari, Yanisha Dwi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study analyzes the financial optimization strategies implemented by treasurers in organizing the Polbeng Business Expo Chapter II, based on three main indicators according to Thamrin, Liana, and Yani (2024): budget planning, cash flow management, and financial risk management. This research employs a descriptive qualitative method with data collected through in-depth interviews, observations, and documentation, involving treasurers from four main events: Ranking 1 Competition, Fashion Show, Coloring Competition, and Singing Competition. The results show that treasurers systematically identified event needs, distinguished between primary and supporting needs, prepared budgets based on price surveys and previous experience, monitored cash flow through recording and projections, and implemented risk mitigation strategies such as reserve funds, expenditure supervision, and vendor down payments. In addition, coordination among committees supported smoother financial control. The application of these strategies supports efficient use of funds, maintains cash flow stability, and minimizes financial risks during event implementation. Compared to previous unstructured financial practices in student activities, this study demonstrates that systematic financial strategies can improve fund management effectiveness, even when implemented by students without professional financial systems. Overall, the study confirms that financial optimization strategies can be effectively adapted in managing student event finances through consistent planning, recording, and control, contributing to successful event execution and financial accountability.